ANALISIS KETERAMPILAN BERPIKIR KREATIF DI MTs NEGERI 3 KOTA SURABAYA - Inayah, Nailil; Mukaromah, Sa’ida Umi (Universitas Tanjungpura, 2025)
21st Century Challenges encourage students to develop creative thinking skills, because creative thinking skills can be used to solve problems or improve thinking skills. Apart from that, the Merdeka curriculum also emphasizes creative thinking skills. This is because it is the basis for increasing students